Средства выражения импликации в художественном тексте (на материале романа Энтони Бёрджесса «Заводной апельсин») - Филенко, С.Э. (Культура народов Причерноморья, 2013)
Данная статья посвящена изучению способов реализации импликации в языке
художественного произведения. Научная новизна работы обусловлена малоизученностью средств,
указывающих на импликацию. При проведении исследования использовался метод интерпретации:
рассматривались фигуры речи и образная система художественного текста в контексте общего
смысла произведения. В результате была установлена специфика выражения импликации в романе
Энтони Бёрджесса «Заводной апельсин», а также определена значимость импликации для
индивидуального стиля писателя.
Ключевые слова: импликация, микроконтекст, вымышленный язык. Подана стаття присвячена вивченню засобів реалiзацiï iмплiкацiï в художньому оповiданнi.
Наукова новизна роботи зумовлена недостатньою вивченістю засобiв, що вказують на iмплiкацiю. При
проведеннi дослідження був використаний метод iнтерпретацiï: були розглянутi фігури мовлення та
образна система художнього тексту в контекстi загального значення оповiдання. В результатi булла
встановлена специфiка вираження iмплiкацiï в романi Ентонi Берджесса «Механiчний апельсин», а
також визначена значущість iмплiкацiï для iндивiдуального стиля письменника.
Ключові слова:iмплiкацiя, мiкроконтекст, вигадана мова. This article covers the study of the ways of realization of implication in language of fiction.
Topicality of the research is determined by currently ever increasing interest on the part of philologists in the
problem of secondary and multiple meanings of works of fiction, and also by necessity to conduct a
comprehensive study of implication as linguistic phenomenon. Scientific novelty of the research is stipulated by
the insufficiently explored means that indicate implication. The main purpose of the scientific investigation is to
discover and decode the language units in which the inner meanings of characters’ thoughts are expressed. The
study is to be conducted on basis of the novel written by the famous English speaking writer of the twentieth
century, Anthony Burgess‘A Clockwork Orange’, which once had made its author popular all over the world.
Problems raised by the author were also emphasized in the novel with the help of peculiar language of
communication of the main characters. The study to be conducted method of interpretation was used: figures of
speech and system of images of the given work of art were explored in context of its general idea. As a result it
was found out that implication in A. Burgess’s novel contains the author's message to the reader and presents
the main idea of the novel: ‘When a man cannot choose he ceases to be a man’. Taking into consideration results
of the research it is possible to say that implication with its various ways of realization found in Anthony
Burgess’s novel ‘A Clockwork Orange’ enriched writer’s individual style and made his work unique.
Key words: implication, micro context, invented language.